Conflict of Authority in Election Disputes: The Shift from the Constitutional Court to Party Courts in Indonesia - Paulus Titaley; Marthinus Johanes Saptenno; Hendrik Salmon; Saartje Sarah Alfons (Khazanah Hukum, 2025)
The general election process in Indonesia faces serious challenges related to the resolution of election disputes. The transfer of authority to resolve election disputes from the Constitutional Court to the internal Party Court has created legal uncertainty and threatens the democratic process. Therefore, the purpose of this research is to analyze the impact of this transfer of authority on people's sovereignty and the integrity of the legal system in Indonesia. This study uses a normative legal method, focusing on applicable legal provisions and legal principles to analyze the implications of this shift in authority. This study finds that the transfer of authority to resolve election disputes to the internal Party Court has created conflicts with the decisions of the Constitutional Court, thereby threatening the principles of accountability and transparency that are essential in democracy. Furthermore, this study also finds that internal political party interests often override constitutional principles. This study concludes that legal and political reforms are necessary to ensure fair resolution of election disputes and maintain democracy in Indonesia. The Constitutional Court must play a crucial role again in resolving election disputes to maintain public trust in the democratic process in Indonesia. Thus, the principles of accountability, transparency, and people's sovereignty can be upheld.